2009
DOI: 10.1007/s00787-009-0048-1
|View full text |Cite
|
Sign up to set email alerts
|

Some clinical characteristics of children who survived the Marmara earthquakes

Abstract: The Marmara earthquakes occurred in the Marmara Region (North West) of Turkey in 1999 and resulted in a death toll of approximately 20,000. This paper investigates the relationships between diagnoses and certain variables in children who developed emotional and/or behavioral disturbances in the aftermath of the Marmara earthquakes and were subsequently seen at a child psychiatry outpatient clinic. The variables evaluated are gender, age, the location where the earthquake was experienced, and the degree of loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…One prospective study of childhood sexual abuse found no association between age at abuse onset and PTSD symptoms 33 . Evidence regarding the effects of age at onset to natural disasters appears more consistent, with both retrospective 34 and prospective studies 35,36 observing higher levels of PTSD symptoms or PTSD diagnoses among older children (around age 7 and above) compared to younger children (those younger than about age 7). However, results for other traumas is less conclusive, with retrospective studies suggesting there are no differences 37,38 in risk for PTSD based on age at onset of trauma, that early-life trauma is more harmful 39,40 , or that middle childhood (ages 6–11) is more strongly associated with PTSD 41 .…”
Section: Introductionmentioning
confidence: 92%
“…One prospective study of childhood sexual abuse found no association between age at abuse onset and PTSD symptoms 33 . Evidence regarding the effects of age at onset to natural disasters appears more consistent, with both retrospective 34 and prospective studies 35,36 observing higher levels of PTSD symptoms or PTSD diagnoses among older children (around age 7 and above) compared to younger children (those younger than about age 7). However, results for other traumas is less conclusive, with retrospective studies suggesting there are no differences 37,38 in risk for PTSD based on age at onset of trauma, that early-life trauma is more harmful 39,40 , or that middle childhood (ages 6–11) is more strongly associated with PTSD 41 .…”
Section: Introductionmentioning
confidence: 92%
“…Children, therefore, could be said to be at double risk after disasters. Although children and adolescents are affected by earthquakes at comparable rates with those of adults in terms of PTSD and depression (Demir et al, 2010;Karakaya et al, 2004) and follow-up studies show that earthquake-related psychopathology may last for years (Ekzi and Braun, 2009;KaramustafalNo?lu et al, 2006;Wolmer et al, 2005), the possible contribution of parental psychopathology to PTSD and depression rates in children is not adequately studied. In a study on Turkish earthquake survivors , child psychopathology was related more to the psychological symptoms of fathers than those of mothers.…”
mentioning
confidence: 95%
“…Several studies point out that those who experience ASD symptoms are likely to develop subsequent psychiatric disorders like PTSD, depression, anxiety, and other debilitating conditions (Bryant et al 2010(Bryant et al , 2011aDemir et al 2010;Koucky et al 2012). Early ASD diagnosis is important for planning and timely preventive programs and activities in reducing the risk of experiencing negative effects of trauma exposure.…”
mentioning
confidence: 98%